2010
DOI: 10.1111/j.1600-0838.2010.01133.x
|View full text |Cite
|
Sign up to set email alerts
|

Effects of exercise training on oxygen uptake in coronary heart disease: a systematic review and meta‐analysis

Abstract: It is not known to what extent exercise programs increase maximal oxygen uptake (VO(2max)) in patients with coronary heart diseases (CHD). The purpose of this study is to determine the effect of exercise interventions on VO(2max) in subjects with CHD. Database search of randomized controlled trials was conducted from PubMed. Studies were included that reported the characteristics and effects of exercise interventions in subjects with CHD, included a non-exercise control group and measured VO(2max) using direct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
39
2
9

Year Published

2011
2011
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 37 publications
4
39
2
9
Order By: Relevance
“…Data of aerobic improvement found in this study are comparable to those described in literature, where percentage increases of VO 2 between 10 and 30% are reported [18]. In this present study, it was observed a percentage increase of VO 2 peak of 16% after applying moderate-intensity aerobic physical exercise.…”
Section: Discussionsupporting
confidence: 81%
“…Data of aerobic improvement found in this study are comparable to those described in literature, where percentage increases of VO 2 between 10 and 30% are reported [18]. In this present study, it was observed a percentage increase of VO 2 peak of 16% after applying moderate-intensity aerobic physical exercise.…”
Section: Discussionsupporting
confidence: 81%
“…Statistically significant but small improvements were seen in exercise capacity in CAD patients both with and without T2D. However, exercise capacity increased an average of ,5%, whereas in previous studies, the improvement in exercise capacity or CV fitness has varied from 14 to even 40% during exercise-based cardiac rehabilitation (29)(30)(31)(32). In our study, the patients had an average of about one MET higher exercise capacity at the baseline in comparison with the patients in previous studies.…”
Section: Effects Of Exercise Training On the CV Risk Profilecontrasting
confidence: 44%
“…11,12 However, effect of later CR entry on cardiovascular fitness and other key CR outcomes has not been examined in the post-CABG population specifically, where different findings may be observed owing to a different early recovery trajectory. Moreover, there may be unique barriers that delay entry to CR in CABG compared with nonsurgical patients.…”
Section: Editorial See P 539mentioning
confidence: 99%
“…Five studies have been published with mixed results, but none have reported results for CABG patients separately. In a subanalysis of a systematic review, Valkeinen et al 12 reported that there was more than a 2-fold greater gain in VȮ 2peak for patients starting CR <3 months after event (n=11 studies) compared with patients who started CR >3 months (n=7 studies) after event (P=0.06). However, the data were unadjusted for baseline measures or correlates of later entry.…”
Section: Consequences Of Longer Wait Timesmentioning
confidence: 99%